PENANGGULANGAN LOST CIRCULATION DENGAN MENGGUNAKAN METODE UNDER BALANCED DRILLING PADA SUMUR Y, BLOK Z - Rizki Ananda Parulian; abdul hamid; Cahaya Rosyidan (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2017)
Drilling operation is process for creating a hole before production operation. “CT” Well and “Y” Well is located at same area which is Z Block. Those wells are vertical offshore wells. “CT” Well had been drilled on 1971 before “Y” Well was drilled on 2009.While drilling “CT” Well occurred total loss circulation on 12 ¼” at 3928 ft and cured with injection of 375 bbl LCM (Loss Circulation Material) with concentration 300 ppb but the loss circulation still occurred. Then total loss circulation occurred again at depth 4343 ft and 4545 ft. It cured with the same method but it didn’t succeed at all. Thus, using blind drilling method is the only option to anticipate the loss. This operation took 17 days using those methods.Well “Y” on 12 ¼” was drilled conventionally. When it reached depth 2910 ft occurred total loss circulation. Based on “CT” Well, using Under Balanced Drilling Method is the best way to anticipate the total loss circulation. This method only took 8 days Keywords : Grid Model Reservoir, Single Porosity, Grid Cell.